Nursing assistance in patient care with external ventricular drain: a scoping review - Victoria Tiyoko Moraes Sakamoto; Tainara Wink Vieira; Karin Viegas; Carine Raquel Blatt; Rita Catalina Aquino Caregnato (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to map the available evidence about nursing care aimed at adult patients using external ventricular drain. Methods: this is a review using the scoping review method. Results: Initially, 965 studies were identified and, after the eligibility criteria, a sample of 54 publications was obtained. Each of them was assessed according to GRADE, resulting in three studies with high quality; 14 with moderate quality; 32 with low quality; and five with very low quality. It was highlighted 20 nursing care subdivided into nine categories, namely: drainage system; bed positioning and mobilization; catheter care; monitoring of intracranial pressure; and medication administration. Conclusions: the scoping review made it possible to identify the main nursing care directed to adult patients undergoing placement of external ventricular drain from the evidence available to date.